Divine Temporality and Providential Bodgery - Mullins, R. T. (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2021)
In contemporary debates, one is presented with temporal and timeless conceptions of divine eternality. Each conception is said to have various consequences for understanding divine perfection and providence. In this paper, I shall consider a pair of arguments against divine temporality that suggest that a temporal God could potentially make mistakes, thus making the temporal God less than perfect. I shall develop these objections, and discuss various ways for the temporalist to reply.